Representasi Gender Pada Iklan Sajiku Seri Ibu Kuat Sajiku (2025) - Afrilia Mustika Damayanti; Laras Kuntiyasari (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to uncover the representation of gender bias in the Sajiku Seasoning Flour Advertisement Series "Strong Mother" (2025) and examine how its visual and narrative construction reinforces women's domestic roles. This advertisement is interesting to study because, despite depicting a strong mother working in the public sphere, she remains the central figure in all household chores. To understand the message conveyed, this study uses a qualitative approach using Roland Barthes's semiotic analysis method, examining the denotative, connotative, and mythical meanings of each scene in the advertisement. The results show that the Sajiku Strong Mother Series advertisement contains several forms of gender bias, including: first, reinforcing the stereotype that housework is a woman's natural responsibility. Second, normalizing the double burden on women, who are portrayed as having to work and care for all family needs without complaint. Third, the absence of a male figure reinforces the notion that domestic matters are not a man's responsibility. Fourth, women's love and self-worth are reduced to their ability to cook and provide household services for their families. Through emotional symbols, narratives, and visuals, this advertisement subtly reproduces patriarchal values ​​and confines women's identities to domestic roles.